A Possible Neurodegeneration Mechanism Triggered by Diabetes. (October 2019) - Farhadi, Aisan; Vosough, Massoud; Zhang, Jin-San; Tahamtani, Yaser; Shahpasand, Koorosh
Abstract : Several conditions result in neurodegeneration; among which diabetes mellitus (DM) is of crucial importance. Tau (τ) malfunction is a major pathological process participating in neurodegeneration. Despite extensive considerations, the actual causative link between DM and τ abnormalities remains uncertain thus far. Phosphorylated (p)-τ at Thr–Pro motifs can exist in the two distinct cis and trans conformations. cis is neurotoxic, and is accumulated upon various stress conditions, such as nutrition depletion. We assume that pathogenic cis p-τ is the central mediator of neurodegeneration in DM, and propose why different brain areas give various responses to stress conditions. We herein juxtapose recent approaches in diabetic neurodegeneration and propose a therapeutic target to stop neuronal loss during DM. Highlights: DM is a major metabolic disorder that may result in neurodegeneration. Disrupted insulin signaling pathway or glucose metabolism deficiency can induce τ hyperphosphorylation. τ is a microtubule-associated protein. It is moderately phosphorylated under physiological conditions but its hyperphosphorylation reflects pathogenicity and is a major pathological hallmark of neurodegeneration. Phosphorylated τ at Thr231 exists in the two distinct cis and trans conformations. cis p-τ is neurotoxic and drives neurodegeneration. cis p-τ is accumulated in cultured neurons upon oxidative stress as well as nutrition depletion.